Polyparasitism with Malaria and Intestinal Parasite Infections among Infants and Preschool-Aged Children in Egbedore, Osun State, Nigeria - S. N. Odoemene; A. S. Oluwole; H. O. Mogaji; M. V. Adegbola; O. O. Omitola; A. A. Bayegun; D. A. Ojo; S. O. Sam-Wobo; U. F. Ekpo (Journal of Parasitology Research)
Polyparasitism is widespread in many communities in Sub-Saharan Africa. However, there is paucity of data on polyparasitism in infants and preschool-aged children (IPSAC), to inform policy developments. Therefore, a survey of 1110 consented IPSAC was undertaken in Egbedore Local Government Area (LGA), Osun State, Nigeria, to determine the prevalence of polyparasitism in IPSAC in ten randomly selected rural communities. Fresh stool and blood samples were collected and processed for intestinal parasites and malaria infection. Mothers/caregivers were interviewed using a structured questionnaire to obtain demographic data of their IPSAC and to document knowledge, attitude, and practice (KAP) on parasitic infections. Data obtained through the questionnaire were analyzed using EpiData version 3.1, while parasitological data were analyzed using Statistical Package for Social Sciences (version 20.0). Descriptive statistics were computed for demographic data and association which were tested using bivariate analysis at a 95% confidence level while significance was set at p<0.05. The results showed that 349 (46.29%) were infected with a single parasite. Infants and preschool-aged children infected with double, triple, and quadruple parasites are 268 (35.54%), 122 (16.18%), and 15 (1.99%), respectively. The prevalence of polyparasitism is 405 (53.71%). Although females (54.07%) were more infected than males (45.93%), there was no significant difference (p>0.05) observed. Significantly (p<0.05) more preschool children (65.93%) harbour more infections than the infants do (34.07%). Ara community (14.81%) had the highest cases of polyparasitized IPSAC, but no significant difference (p>0.05) was observed across the communities. Double parasitic infection of Plasmodium falciparum and Ascaris lumbricoides (30.12%) and triple parasitic infection of P. falciparum, A. lumbricoides, and T. trichiura (14.81%) were the most common forms of polyparasitism encountered in the study. This study showed that polyparasitism is a burden in IPSAC and needs further investigation.